Electrical Properties of Frog Saccular Hair Cells: Distortion by Enzymatic Dissociation - Armstrong, Cecilia E. (J Neurosci, 1998)
Although it is widely accepted that the electrical resonance seen in many types of auditory and vestibular hair cells contributes to frequency selectivity in these sensory systems, unexplained discrepancies in the frequency (f) and sharpness (Q) of tuning have raised serious questions. For example, enzymatically dissociated hair cells from bullfrog (Rana catesbeiana) sacculus resonate at frequencies well above the range of auditory and seismic stimuli to which the sacculus is most responsive. Such disparities, in addition to others, have led to the proposal that electrical resonance alone cannot account for frequency tuning. Using grassfrog (Rana pipiens) saccular hair cells, we show that the reported discrepancies in f andQ in this organ can be explained by the deleterious effects of enzyme (papain) exposure during cell dissociation. In patch-clamp studies of hair cells in a semi-intact epithelial preparation, we observed a variety of voltage behaviors with frequencies of 35–75 Hz. This range is well below the range of resonant frequencies observed in enzymatically dissociated hair cells and more in tune with the frequency range of natural stimuli to which the sacculus is maximally responsive. The sharpness of tuning also agreed with previous studies using natural stimuli. In contrast to results from enzymatically dissociated hair cells, both a calcium-activated K(+) (K(Ca)) current and a voltage-dependent K(+)(K(V)) current contributed to the oscillatory responses of hair cells in the semi-intact preparation. The properties of the K(Ca) and the Ca(2+) current were altered by enzymatic dissociation. K(V) and a small-conductance calcium-activated K(+) current were apparently eliminated.